The Impact of Calcium Hydroxide on the Osteoinductive Capacity of Demineralized Freeze-Dried Bone Allograft: an In-Vitro Study - Hengameh Khosropanah; Nazila Lashkarizadeh; Maryam Ayatollahi; Maryam Kaviani; Zohreh Mostafavipour (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: A great challenge in periodontal therapy is the regeneration enhancement of osseous defects through applying osteoinductive materials. Demineralized freeze-dried bone allograft (DFDBA) has already been introduced as an allograft with osteoconductive and variable osteoinductive properties. Calcium hydroxide [Ca(OH)2] is an available well-known material in dentistry, which induces hard tissue formation. Purpose: This study evaluated the efficiency of combination of DFDBA and Ca(OH)2 in improving the quality of osteoinduction of DFDBA. Materials and Method: Human bone marrow-derived mesenchymal stem cells were taken from volunteers' iliac crest. Cell proliferation was determined by MTT test at 18, 24 and 48 hours post-culture in 10 groups. The employed material were 0.5, 1.0 mg/ml Ca(OH)2 in two forms of suspension and pH-adjusted solution, 10mg/ml DFDBA per se and in combination with 0.5 and 1.0 mg/ml Ca(OH)2. Mineralization was assessed by Alizarin red staining in 10 mg/ml DFDBA, DFDBA+ 0.5 and 1 mg/ml Ca(OH)2 in solution and suspension forms. The data were statistically analyzed by using one-way ANOVA and Tukey's post-hoc test (p< 0.05). Results: The pH-adjusted solutions exhibited better cell proliferation compared with the suspension groups. The combination of 0.5mg/ml Ca(OH)2 solution and DFDBA increased the cell proliferation and mineralization compared with DFDBA per se (p= 0.033). Conclusion: The combination of Ca(OH)2 with DFDBA improved the osteoinductivity of DFDBA.